2017
DOI: 10.1155/2017/3048013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Choroidal Neovascularization Shown by OCT Angiography and Choroidal Thickness in Patients with Chronic Central Serous Chorioretinopathy

Abstract: Purpose To assess the occurrence of choroidal neovascularization (CNV) secondary to chronic central serous chorioretinopathy (CSCR) using optical coherence tomography angiography (OCTA) and correlate these findings with choroidal thickness (CT). Materials and Methods This retrospective study included 25 consecutive patients (43 eyes), mean age 48.12 ± 7.8 years, diagnosed with persistent CSCR. All patients underwent a complete ophthalmic examination, fluorescein angiography (FA), indocyanine green angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…[7] OCTA enables reproducible, quantitative assessment of the macular microcirculation in the macula and may be used in diagnosing different retinal diseases, such as diabetic retinopathy, central serous chorioretinopathy and age-related macular degeneration. [810] OCTA provides three-dimensional maps of the macular perfusion and seems to be a promising method in the detection of early microcirculation disorders. To the best of our knowledge there are few reports on retinal perfusion in myopic adults using this method but no previous reports on OCTA findings in myopic children.…”
Section: Introductionmentioning
confidence: 99%
“…[7] OCTA enables reproducible, quantitative assessment of the macular microcirculation in the macula and may be used in diagnosing different retinal diseases, such as diabetic retinopathy, central serous chorioretinopathy and age-related macular degeneration. [810] OCTA provides three-dimensional maps of the macular perfusion and seems to be a promising method in the detection of early microcirculation disorders. To the best of our knowledge there are few reports on retinal perfusion in myopic adults using this method but no previous reports on OCTA findings in myopic children.…”
Section: Introductionmentioning
confidence: 99%
“…Use of OCTA has expanded facility in detecting nonexudative macular neovascularization or mimicking situations. The prevalence range of macular neovascularization diagnosis using OCTA in chronic CSC is 8.3-44.8% [65][66][67][68][69][70][71]. These results provided by OCTA are much better than those from isolated IVFA.…”
Section: Complementary Analysismentioning
confidence: 88%
“…Multifocal leak zones without correspondence in IVFA [5,6,17,35] OCT CT > 500 micron [25] PED height > 50 micron [59] Large amount or recurrent subretinal fluid [9,14] Choroidal hyperreflective dots [9,10,14] Hyperreflective choroidal vessel walls [9,10,14] Intra-and subretinal hyperreflective dots and material [60] Thinning and atrophy of the outer nuclear layer [61] External limiting membrane discontinuity [62] Cystoid degeneration [11] Elongation of the photoreceptor outer segments [9,10,32] Double sign at external retina (irregular, flat, and dense RPE detachment) [65] Fibrinoid reaction [9,10] Pigment deposition [9,10,32] Choroidal rift [58] Reduced ganglion cell complex thickness [64] OCTA Subretinal neovascularization [65][66][67][68][69][70][71] Flow void zones [72,73]…”
Section: Icgmentioning
confidence: 99%
“…Localization of the RPE defect might be performed with SS-OCTA in selected cases; if this finding can be confirmed in larger patient populations, perhaps laser photocoagulation could be employed, based on this information, without the need for invasive diagnostic tools. The diagnosis of CNV complicating or simultaneous to CSC is demanding 11 and not infrequent. A recent OCT-based study confirmed CNV complicating CSC in 17.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of CNV complicating or simultaneous to CSC is demanding 11 and not infrequent. A recent OCT-based study confirmed CNV complicating CSC in 17.6% of cases.…”
Section: Discussionmentioning
confidence: 99%